2020
DOI: 10.3389/fvets.2020.00562
|View full text |Cite|
|
Sign up to set email alerts
|

Dairy Calves in Uruguay Are Reservoirs of Zoonotic Subtypes of Cryptosporidium parvum and Pose a Potential Risk of Surface Water Contamination

Abstract: surface water to supply ∼1,700,000 people. Infected calves on all farms were within 20-900 m of a natural surface watercourse draining the farmland, 10 of which flowed into six water treatment plants located 9-108 km downstream. Four watercourses flowed downstream into Aguas Corrientes. Calves are reservoirs of zoonotic C. parvum subtypes in Uruguay and pose a public health risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
(118 reference statements)
2
6
0
Order By: Relevance
“…In western mainland Europe, the IIaA15G2R1 subtype was previously described as the most prevalent in cattle [36,37,40,[42][43][44]. Similar observations were reported in other European countries, including Portugal, Italy, Spain, Germany, Czech Republic, Austria, Slovenia, and the United Kingdom [20,51,52,54,55,57,66,67,88] and in other parts of the world such as Japan and Uruguay [89,90].…”
Section: Discussionsupporting
confidence: 81%
“…In western mainland Europe, the IIaA15G2R1 subtype was previously described as the most prevalent in cattle [36,37,40,[42][43][44]. Similar observations were reported in other European countries, including Portugal, Italy, Spain, Germany, Czech Republic, Austria, Slovenia, and the United Kingdom [20,51,52,54,55,57,66,67,88] and in other parts of the world such as Japan and Uruguay [89,90].…”
Section: Discussionsupporting
confidence: 81%
“…Given the geographic proximity of the dairy calf rearing areas and natural surface watersources in Uruguay, the dense network of rivers and the relatively high annual rainfalls and occasional flooding events in this country, calves pose a risk for surface water contamination with fecal pathogens, notably Cryptosporidium spp. [50]. Because some subtypes of Cryptosporidium parvum are zoonotic and cattle are reservoir of potentially zoonotic strains [51,52], and considering that Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…has been identified as a cause of diarrhea in children in Uruguay [ 53 ], we further speciated and subtyped the cryptosporidia detected in calves in this study. Interestingly, of seven C. parvum subtypes detected in 166 calves, five subtypes detected in 143 calves from nearly all farms had been detected in humans elsewhere and have zoonotic potential [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the assembly done here to our knowledge represents the first IIaA17G2R1 subtype isolate for which long read sequencing has been performed. C. parvum belonging to the IIaA17G2R1 subtype have been identified in farms in various regions of the world [33][34][35], was the second most common genotype identified in human cases in a recent study done in Canada [36] and is responsible for causing foodborne outbreaks in the US [37,38] Published studies have shown the presence of contingency genes in Cryptosporidium spp., which are responsible for surmounting challenges from the host and are subject to spontaneous mutation rates [39][40][41]. The majority of these genes are located in the telomere regions of the chromosomes, which are prime sites that evolve and mediate host-parasite interactions [30,42].…”
Section: Discussionmentioning
confidence: 99%